Multiscale Functional Metal Architectures by Antibody‐Guided Metallization of Specific Protein Assemblies in Ex Vivo Multicellular Organisms. Issue 35 (3rd August 2022) - Song, Chang Woo; Song, Dae‐Hyeon; Kang, Dong Gyu; Park, Ki Hyun; Park, Chan E; Kim, Hyunwoo; Hur, Yongsuk; Jo, Sung Duk; Nam, Yoon Sung; Yeom, Jihyeon; Han, Seung Min; Chang, Jae‐Byum
Abstract: Biological systems consist of hierarchical protein structures, each of which has unique 3D geometries optimized for specific functions. In the past decades, the growth of inorganic materials on specific proteins has attracted considerable attention. However, the use of specific proteins as templates has only been demonstrated in relatively simple organisms, such as viruses, limiting the range of structures that can be used as scaffolds. This study proposes a method for synthesizing metallic structures that resemble the 3D assemblies of specific proteins in mammalian cells and animal tissues. Using 1.4 nm nanogold‐conjugated antibodies, specific proteins within cells and ex vivo tissues are labeled, and then the nanogold acts as nucleation sites for growth of metal particles. As proof of concept, various metal particles are grown using microtubules in cells as templates. The metal‐containing cells are applied as catalysts and show catalytic stability in liquid‐phase reactions due to the rigid support provided by the microtubules. Finally, this method is used to produce metal structures that replicate the specific protein assemblies of neurons in the mouse brain or the extracellular matrices in the mouse kidney and heart. This new biotemplating approach can facilitate the conversion of specific protein structures into metallic forms in ex vivo multicellular organisms. Abstract : The synthesis of metallic structures mimicking the specific protein assemblies in multicellular organisms, such as human cells and animal tissue, is demonstrated via antibody–antigen interactions and electroless deposition. This work enables the use of diverse protein structures that are arranged in unique 3D geometries optimized for certain functions as scaffolds for biotemplating.